2011
DOI: 10.1055/s-0030-1271162
|View full text |Cite
|
Sign up to set email alerts
|

Geschlechtsspezifische Wahrnehmung des orthopädisch-unfallchirurgischen Berufsbilds während des Medizinstudiums

Abstract: It seems that there is great interest in the fields of orthopaedic trauma among both female and male students in the middle portion of their studies. Women, especially, tend to prefer a specialisation in this operative field early in the course of their studies. However, this pool of potential successors decreases dramatically with time, due to personal experiences garnered on the wards, expectations regarding career paths (male-dominated, long hours) as well as concerns about family planning. The most dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
1
3
0
3
Order By: Relevance
“…According to the students’ opinion, arthroscopy and MSUS have the potency to raise interest in surgery. This is in line with an earlier report by our study group that showed that students develop an interest in orthopaedic trauma at a very early level but somehow lose it over time due to negative experience during their clinical training [25]. In times of shortage of young academics, this is a very important factor that is amenable to intervention.…”
Section: Discussionsupporting
confidence: 90%
“…According to the students’ opinion, arthroscopy and MSUS have the potency to raise interest in surgery. This is in line with an earlier report by our study group that showed that students develop an interest in orthopaedic trauma at a very early level but somehow lose it over time due to negative experience during their clinical training [25]. In times of shortage of young academics, this is a very important factor that is amenable to intervention.…”
Section: Discussionsupporting
confidence: 90%
“… 56 Female students pursuing a surgical career have experienced discrimination, 37 , 38 , 57 , 53 although this is not an isolated phenomenon for the specialty: female students interested in a career in orthopedic trauma, or male students interested in obstetrics had such experiences. 37 , 38 , 58 , 59 It is not clear if gender itself is a factor that affects the learning of fundamental surgical skills. 24 - 35 Work experience, interest in surgery, training and previous video game experience seem to enhance the surgical skills of medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Gender and associated gender roles are reported to have an impact on learning and skills acquisition [13] and an influence on specialty preferences [14]. With rising numbers of women in medical school these differences warrant further evaluation in order to accommodate the educational needs of both genders.…”
Section: Introductionmentioning
confidence: 99%